Immunomodulatory Therapeutic Strategies in Stroke - Malone, Kyle; Amu, Sylvie; Moore, Anne C.; Waeber, Christian (Frontiers in Pharmacology, 2019)
The role of immunity in all stages of stroke is increasingly being recognised, from the pathogenesis of risk factors to tissue repair, leading to the investigation of a range of immunomodulatory therapies. In the acute phase of stroke, proposed therapies include drugs targeting pro-inflammatory cytokines, matrix metalloproteinases, and leukocyte infiltration, with a key objective to reduce initial brain cell toxicity. Systemically, the early stages of stroke are also characterised by stroke-induced immunosuppression, where downregulation of host defences predisposes patients to infection. Therefore, strategies to modulate innate immunity post-stroke have garnered greater attention. A complementary objective is to reduce longer term sequelae, by focusing on adaptive immunity. Following stroke onset, the integrity of the blood-brain barrier is compromised, exposing central nervous system (CNS) antigens to systemic adaptive immune recognition, potentially inducing autoimmunity. Some pre-clinical efforts have been made to tolerise the immune system to CNS antigens pre-stroke. Separately, immune cell populations which exhibit a regulatory phenotype (T and B regulatory cells) have been shown to ameliorate post-stroke inflammation and contribute to tissue repair. Cell-based therapies, established in oncology and transplantation, could become a strategy to treat the acute and chronic stages of stroke. Furthermore, a role for the gut microbiota in ischemic injury has received attention. Finally, the immune system may play a role in remote ischemic preconditioning-mediated neuroprotection against stroke. The development of stroke therapies involving organs distant to the infarct site, therefore, should not be overlooked. This review will discuss the immune mechanisms of various therapeutic strategies, surveying published data and discussing more theoretical mechanisms of action that have yet to be exploited.